Wage equality between men and women: defenses and exceptions - Blume Moore, Iván (2019)
Since the expedition of a series of laws that prohibit wage inequality between men and women, the effectivity of such prohibition in Peru has become more visible. Regardless, the prohibition of wage inequality does not operate as an absolute, where certain exceptions and justification to the wage imbalance between men and women can be allowed. This article explores the relevant laws and highlights the exceptions and justifications to wage inequality, examining the cases where these can be evidenced.